Bifidobacterium adolescentis Alleviates Liver Steatosis and Steatohepatitis by Increasing Fibroblast Growth Factor 21 Sensitivity - Long, Xiaoxue; Liu, Dan; Gao, Qiongmei; Ni, Jiacheng; Qian, Lingling; Ni, Yueqiong; Fang, Qichen; Jia, Weiping; Li, Huating (Frontiers in Endocrinology, 2021)
The gut microbiota is a newly identified contributor to the development of non-alcoholic fatty liver disease (NAFLD). Previous studies of Bifidobacterium adolescentis (B. adolescentis), a species of Bifidobacterium that is common in the human intestinal tract, have demonstrated that it can alleviate liver steatosis and steatohepatitis. Considering the protective effect of fibroblast growth factor 21 (FGF21) analogs on NAFLD, we wondered whether treatment with B. adolescentis would alleviate NAFLD. To this end, male C57BL/6J mice on a choline-deficient high-fat diet (CDHFD) were treated with drinking water supplemented with B. adolescentis for 8 weeks, followed by the acute administration of recombinant mouse FGF21 protein (rmFGF21). B. adolescentis supplementation reversed the CDHFD-induced liver steatosis and steatohepatitis. This was evaluated based on the NAFLD activity score (NAS), reduced liver enzymes, and lipid accumulation. Further studies demonstrated that B. adolescentis supplementation preserved the gut barrier and reduced gut microbiota-derived lipopolysaccharide (LPS). The results of acute administration of rmFGF21 showed that B. adolescentis supplementation alleviated the CDHFD-induced FGF21 resistance. This was accompanied by elevated expressions of β-klotho (KLB) in the liver. Collectively, this study showed that B. adolescentis supplementation could alleviate NAFLD by increasing FGF21 sensitivity. Hence, B. adolescentis may be a novel target for the treatment of NAFLD/nonalcoholic steatohepatitis (NASH).